Determinants of Health‐Related Quality of Life in Children and Adolescents With Type 1 Diabetes: A Cross‐Sectional Study - Solmaz Heidari; Majid Aminzadeh; Ronak Badiei; Mahtab Tamimi; Shooka Mohammadi (Health Science Reports, 2026)
ABSTRACT Background and Aim Type 1 diabetes mellitus (T1DM) is a chronic condition that affects emotional, physical, social, and academic functioning of children and adolescents. Assessing health‐related quality of life (HRQoL) provides insight into the broader impact of T1DM. This study evaluated HRQoL among pediatric patients with T1DM in southwest Iran using reports from children and parents. Methods This cross‐sectional study included 234 children aged 5–16 years with T1DM and their parents at Abuzar Hospital (Ahvaz, Iran). HRQoL was assessed using the Pediatric Quality of Life Inventory (PedsQL) version 4.0 completed by both children and parents, and the PedsQL 3.2 Diabetes Module. Demographic, clinical, and lifestyle characteristics were collected. Results Children reported the highest scores for physical functioning and the lowest scores for school functioning. Parents rated their children's HRQoL significantly lower than children did across all domains ( p < 0.001). Boys had significantly higher HRQoL than girls in all generic domains except school functioning and in all diabetes‐specific domains ( p < 0.05). Children reported higher HRQoL than adolescents, with significant differences in most domains except physical functioning ( p < 0.05). Common unhealthy behaviors included physical inactivity (31.6%), breakfast skipping (31.2%), and weekly fast‐food consumption (43.2%). Only 26.5% of participants consistently practiced carbohydrate counting. Multivariable linear regression analysis showed that male sex, regular physical activity, and consistent carbohydrate counting were independently associated with higher total PedsQL scores ( p < 0.05). Conclusion Pediatric patients with T1DM in this study had the lowest HRQoL scores in school functioning. Differences between children's and parents' reports suggest that parents may perceive a greater impact of diabetes than children. Lower HRQoL among girls highlights the need for additional psychosocial support. Routine HRQoL assessment, psychosocial support, regular physical activity, carbohydrate counting education, and family‐centered care may improve overall well‐being in these patients.